2021
DOI: 10.1080/21655979.2021.1964889
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role of early growth response-1 in liver cancer through the regulation of the microRNA-675/sestrin 3 and the Wnt/β-catenin signaling pathway

Abstract: Early growth response-1 (EGR1) is a multi-domain protein and an immediate early transcription factor that is induced during liver injury and controls the expression of a variety of genes implicated in metabolism, cell proliferation, and tumorigenesis. Liver cancer (LC) is a highly malignant disease with high mortality worldwide. This study focused on the function of EGR1 in LC development and the mechanism of action. Two LC-related datasets GSE101728 and GSE138178 downloaded from the Gene Expression Omnibus (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Wnt signaling pathway contributes to EMT when extracellular E-cadherin is degraded, β-catenin is able to translocate into the nucleus to induces EMT [ 30–32 ]. The deregulation of Wnt signaling is implicated in the progression of various cancers, such as papillary thyroid cancer [ 33 ], glioblastoma [ 34 ], breast cancer [ 35 ] and liver cancer [ 36 ]. In CRC, TGF-beta1 positively regulates B7-H4 through miR-155/miR-143 axis, thereby promoting cancer cells immune escape [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway contributes to EMT when extracellular E-cadherin is degraded, β-catenin is able to translocate into the nucleus to induces EMT [ 30–32 ]. The deregulation of Wnt signaling is implicated in the progression of various cancers, such as papillary thyroid cancer [ 33 ], glioblastoma [ 34 ], breast cancer [ 35 ] and liver cancer [ 36 ]. In CRC, TGF-beta1 positively regulates B7-H4 through miR-155/miR-143 axis, thereby promoting cancer cells immune escape [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that SESN3 represents a core mediator of ROS downstream of the AKT signaling pathway and FOXO transcriptional factors [ 35 ]. Also, it was identified as the downstream target of miR-675 in liver cancer [ 36 ]. The bioinformatics prediction conducted in the present study also verified that SESN3 was not only a gene enriched in the PI3K/AKT signaling, but also a putative target of miR-375 in ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two LC-related datasets, GSE101728 and GSE138178, obtained from the Gene Expression Omnibus (GEO) database, were used to specify essential genes involved in cancer progression. Microarray analysis was conducted to determine differentially expressed miRs after EGR1 knockdown [ 91 ]. The target gene of miR-675 was identified by integrated analysis.…”
Section: Function Of Oncogenic Mirs In Hepatocellular Carcinomamentioning
confidence: 99%
“…EGR1 and miR-675 activated Wnt/β-catenin through down-regulating SESN3. This analysis demonstrated that EGR1 promotes the malignant behaviors of LC cells by mediating the miR-675/SESN3/Wnt/β-catenin axis [ 91 ].…”
Section: Function Of Oncogenic Mirs In Hepatocellular Carcinomamentioning
confidence: 99%